Method for separating aluminum, iron, lithium and gallium from industrial solid waste hydrochloric acid leachate in one step
By adding a DC electric field to the polymer coated film electrodialysis system, selectively transported polymer coated film is prepared, and one-step efficient separation of aluminum, iron, lithium and gallium from the industrial solid waste hydrochloric acid leaching liquid is achieved, solving the problems of long process and low efficiency in the existing technology, and it is environmentally friendly.
Patent Information
- Application Number
- CN202510117490.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to effectively separate aluminum, iron, lithium and gallium from the industrial solid waste hydrochloric acid leaching liquid in one step, and the process is long and the efficiency is low, and the cost of extraction alone is high.
By adding a direct current electric field to the polymer coated film (PIM), a polymer coated film that selectively transports iron and gallium and a polymer coated film that selectively transports lithium are prepared to construct a polymer coated film electrodialysis system to achieve directional migration and separation and enrichment of multiple ions.
It realizes one-step efficient separation of aluminum, iron, lithium and gallium, simplifies the process, reduces the drug consumption, avoids the problems of large and difficult to recover the extractant in traditional extraction processes, and is environmentally friendly.
Smart Images

Figure CN119900054A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of valuable metal recovery, and in particular relates to a method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leaching solution in one step. Background Art
[0002] Lithium (Li) is an important "energy metal" in the 21st century and is widely used in new energy development, electronic communications, aerospace and other fields. In recent years, the rapid development of new energy vehicles has continuously increased the demand for lithium resources. Gallium (Ga) is an important rare metal. With the vigorous development of the semiconductor industry, the demand for gallium continues to rise. It is estimated that by 2050, the demand for gallium will be about 10 times the current level. Aluminum is a strategic mineral resource. my country's bauxite resources are in short supply and its external dependence is 60%. Due to the continuous growth in demand for aluminum, lithium, gallium, etc., the recovery of aluminum, lithium and gallium resources from industrial solid wastes such as fly ash, coal gangue, electrolytic aluminum slag, red mud, and metallurgical fly ash has attracted widespread attention. Recovering strategic metals from solid waste can not only improve resource utilization, but also open up new channels for strategic metal supply and realize high-value utilization of industrial solid waste resources. At present, the extraction of aluminum, lithium and gallium from industrial solid waste mainly includes alkaline and acid processes. The acid process is simple, short and produces less slag. However, the leaching solution obtained after acid leaching is a complex acidic system with high ionic strength and coexistence of multiple ions. The target metal lithium and gallium content is very low, and there is H + and Li + Due to the competition, ion selective separation is difficult.
[0003] At present, there are some reports on the extraction of strategic metals such as aluminum, lithium and gallium from industrial solid waste acidic systems, including solvent extraction and ion imprinting methods, but they mainly focus on single extraction. For example, Liu Xuguang's research group at Taiyuan University of Technology developed ion imprinting materials for the separation of lithium ions and gallium ions in fly ash acidic leaching solutions, and prepared crown ether functionalized lithium ion imprinting materials (Li + -IIM) in an acidic medium with pH = 1.0 and a lithium ion concentration of 40 mg / L, + The adsorption capacity of the prepared carboxyl-functionalized gallium imprinted material (IIP-GO / PAA) is 16.40 mg / g in an acidic medium with a pH of 3.0 and a gallium ion concentration of 200 mg / L. 3+ The adsorption capacity of Al 3+ , Fe 3+ Mg2+ and Ca 2+ The high selectivity of (Preparation of graphene-based surface ion-imprinted adsorbent for Ga selective extraction from acid leaching of flyash, published in Separation and Purification technology in 2023). Chinese patent CN108265176B reports a method for extracting lithium from fly ash, using a TBP-FeCl3-kerosene extraction system to extract lithium from fly ash acid leaching solution, and obtaining a LiCl solution after multi-stage countercurrent extraction and stripping, with a total lithium recovery rate of 93.1%. However, for the multi-complex system of solid waste, the lithium-gallium content is low (ppm level), the cost of extraction alone is high, and the economy is poor. It is necessary to develop a multi-resource synergistic extraction process of aluminum, lithium, and gallium. Cheng Fangqin of Shanxi University disclosed a method for the synergistic extraction of aluminum iron lithium gallium from high-aluminum solid waste acidic system (CN115418478B), firstly, TBP is used to synergistically extract Li, Fe, and Ga from the hydrochloric acid leaching solution of high-aluminum solid waste, and the remaining aluminum-rich raffinate can be directly used to prepare high-purity aluminum products; the organic phase loaded with Li, Fe, and Ga is then separated by step stripping. Although the above method can realize the extraction and separation of multiple strategic metals in complex solid waste systems, it has problems such as long process and high consumption of reagents in the extraction / stripping process.
[0004] Liquid membrane separation is a non-equilibrium mass transfer process that can achieve simultaneous extraction and stripping processes; polymer-coated membrane (PIM) is developed on the basis of supported liquid membrane. By constructing a uniform and stable film composed of a carrier, a plasticizer and a base polymer, in which the carrier and the plasticizer are fixed between the entangled chains of the base polymer by van der Waals forces and hydrogen bonds, the leakage of the carrier into the aqueous phase can be effectively avoided. The number of carriers required is small, the impact on the environment is low, and it has excellent transport performance, high selectivity and high stability. Cai et al. used PIM prepared from trifluoroacetone (TTA), trioctylphosphine oxide (TOPO) and cellulose triacetate (CTA) to extract Na + and K + Recovery of Li from mixed solution + , Li + The recovery rate was 88.1%, and the separation coefficients of Li / Na and Li / K were 54.25 and 50.60, respectively. However, CTA-based PIM is only suitable for Li in weak alkaline systems. +Patent CN115418676A discloses a method for separating multiple valuable metals from waste lithium battery acid leaching solution in one step, using PVDF-HFP as the base polymer, Aliquat 336 and trioctylamine (TOA) as carriers to prepare two PIMs, and by adding the coordination compound NH4SCN to regulate the Li + 、Co 2+ 、Ni 2+ The ion existence form of the three metal ions is realized under the action of the electric field. However, the components of industrial solid wastes such as fly ash, coal gangue, and red mud are very complex, and there are many types of metal ions in the acid leaching solution, and Li + , Ga 3+ With coexisting ions Al 3+ , Fe 3+ The concentration difference is large and the selective separation is difficult. So far, there is no report on the use of polymer-coated membranes for the synergistic extraction of multiple valuable elements in multi-component complex acidic systems of solid waste. Summary of the invention
[0005] Aiming at the problem that multiple ions such as Al, Fe, Li and Ga coexist in hydrochloric acid leachate of industrial solid waste, the conventional extraction separation and recovery process is long and inefficient, the present invention provides a method for separating Al, Fe, Li and Ga from a complex acidic chlorination system in one step. By adding a direct current electric field on the basis of PIM, the high stability of PIM, the high selectivity for target ions and the strong driving effect of the electric field force on the ion transmembrane transport process are combined to achieve the one-step separation and recovery of Al, Fe, Li and Ga.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leaching solution in one step, comprising the following steps:
[0008] Step 1: Prepare a polymer-coated anion membrane that selectively transmits iron and gallium;
[0009] Step 2: preparing a polymer-coated cation membrane for selective lithium transport;
[0010] Step 3: Establishing a polymer-coated membrane electrodialysis system;
[0011] Step 4: Use a polymer-coated membrane electrodialysis system to treat the hydrochloric acid leaching solution of industrial solid waste containing aluminum, iron, lithium and gallium.
[0012] Furthermore, the step 1 specifically includes: mixing and dissolving a base polymer, a carrier, and a plasticizer in an organic solvent to obtain a casting solution; coating the casting solution on a glass plate, and taking it out after the solvent evaporates to obtain a polymer coating film; wherein the base polymer is one or more of polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), and polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), the carrier is one or more of methyl trioctyl ammonium chloride (Aliquat 336) and trihexyl (tetradecyl) chlorophosphine (Cyphos IL 101), and the plasticizer is one or more of 2-nitrophenyl octyl ether (2-NPOE), trioctyl phosphate (T2EHP), and 2-nitrophenyl pentyl ether (2-NPPE), and the mass percentages of the base polymer, the carrier, and the plasticizer in the polymer coating film are 70% to 80%, 15% to 25%, and 0 to 5%, respectively.
[0013] Furthermore, the step 2 specifically includes: mixing the base polymer and the carrier and dissolving them in an organic solvent to obtain a casting solution; coating the casting solution on a glass plate, taking it out after the solvent evaporates, and obtaining a polymer-coated cation film; wherein the base polymer is one or more of polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), the carrier is an organic phase loaded with lithium ions, and the mass percentages of the base polymer and the carrier in the polymer-coated cation film are 45% to 65% and 35% to 55%, respectively.
[0014] Furthermore, the preparation method of the organic phase loaded with lithium ions is as follows: one or more of tributyl phosphate (TBP), triisobutyl phosphate (TIBP), and N,N-bis(1-methylheptyl)acetamide (N503) are mixed with 1-hydroxyethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt at a volume ratio of 1:0.2 to 1:5, and then mixed with a LiCl solution with a lithium ion concentration of 1g / L to 6g / L at a volume ratio of 1:1, stirred, and centrifuged to separate the phases.
[0015] Furthermore, the organic solvent is one or more of tetrahydrofuran (THF), N,N-dimethylformamide (DMF), and dichloromethane.
[0016] Furthermore, the solvent is evaporated under the following conditions: evaporation at 22±3°C for 12 to 24 hours.
[0017] Furthermore, the polymer-coated membrane electrodialysis system in step 3 comprises an anode receiving chamber, a feed chamber, a cathode receiving chamber and a cathode electrode chamber which are connected in sequence, a polymer-coated membrane anion membrane is arranged between the anode receiving chamber and the feed chamber, a polymer-coated membrane cation membrane is arranged between the feed chamber and the cathode receiving chamber, an anion exchange membrane is arranged between the cathode receiving chamber and the cathode electrode chamber, and electrode plates are arranged on the outer sides of the cathode electrode chamber and the anode receiving chamber, which are respectively connected to the negative electrode and the positive electrode of the power supply.
[0018] Furthermore, the specific process of step 4 is: pumping the feed liquid, receiving liquid and electrode liquid into the corresponding chambers for circulation; wherein the feed liquid is pumped into the feed chamber, the anode receiving liquid is pumped into the anode receiving chamber, the cathode receiving liquid is pumped into the cathode receiving chamber, and the cathode electrode liquid is pumped into the cathode electrode chamber; applying a DC voltage on both sides of the polymer coated membrane electrodialysis system, and under the action of electric drive and the selective permeability of the polymer coated membrane, the directional migration and separation and enrichment of multiple ions are achieved.
[0019] Furthermore, the feed liquid is a hydrochloric acid leaching solution of industrial solid waste containing Al, Fe, Li, and Ga, with a pH value of 0-1, the cathode receiving liquid is a 0.1-0.5 mol / L HCl solution, the anode receiving liquid is a 0.1-0.5 mol / L H2SO4 solution, and the cathode electrode liquid is a 0.1 mol / L H2SO4 solution; each feed liquid is pumped into the chamber at a flow rate of 100 mL / min to circulate in each chamber; the current density of the electrodialysis process is controlled to be 7-20 mA / cm 2 .
[0020] Furthermore, the industrial solid waste is one or more of coal gangue, fly ash, and red mud.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention utilizes Fe 3+ , Ga 3+ Formation of FeCl4 in hydrochloric acid system - 、GaCl4 - complex anion, and Li + 、Al 3+ The properties of the hydrated positive ions are different, and the FeCl4 - 、GaCl4 - Aliquat 336 with high selectivity and good conductivity was used as anion membrane carrier, and neutral ligands preloaded with lithium and ionic liquids were used as cation membrane carriers to prepare polymer-coated membranes, and a polymer-coated membrane electrodialysis coupling system was constructed to achieve FeCl4 under electric drive. - 、GaCl4 - , Li +The cation membrane carrier significantly reduces the membrane surface resistance after loading lithium, and has a positive effect on Li + It shows excellent selectivity. The separation process is simple to operate, and the carrier consumption in the preparation process of the polymer-coated membrane is small, which avoids the problems of large consumption of extractant, loss of extractant and difficulty in recovery caused by the cumbersome extraction / stripping step-by-step operation in the traditional extraction process. It can achieve efficient separation of iron, gallium, aluminum and lithium in one step, and is an environmentally friendly separation system. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the construction of a polymer-coated membrane electrodialysis system.
[0024] Figure 2 It is a schematic diagram of the transport experiment of the polymer-coated membrane electrodialysis system. DETAILED DESCRIPTION
[0025] The examples described below are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operating procedures, but do not limit the protection scope of the patent of the present invention. Any technical solution obtained in the form of equivalent replacement or equivalent transformation should fall within the protection scope of the present invention.
[0026] Example 1
[0027] (1) Preparation of polymer-coated anion membrane: 0.7 g PVDF, 0.25 g Aliquat 336 and 0.05 g 2-NPOE were mixed and dissolved in 10 mL DMF and magnetically stirred for 12 h to obtain a casting solution. The casting solution was then poured onto a 15×15 cm glass plate and evaporated at room temperature for 24 h. The membrane was naturally peeled off with deionized water to obtain a polymer-coated anion membrane.
[0028] (2) Preparation of polymer coated cationic membrane: tributyl phosphate (TBP) and 1-hydroxyethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt ([HOEmim][NTf2]) were mixed in a volume ratio of 1:0.2, and a LiCl solution with a lithium ion concentration of 6 g / L was added at an O / A ratio of 1:1. After stirring for 30 minutes, the phases were separated by centrifugation to obtain an organic phase (TBP-[HOEmim][NTf2]-Li) with a lithium loading concentration of 2.70 g / L as a carrier; 0.5 g PVDF and 0.6 g TBP-[HOEmim][NTf2]-Li were mixed and dissolved in 10 mL DMF, and magnetically stirred for 12 h to obtain a casting solution; the casting solution was then poured onto a 15×15 cm glass plate, evaporated at room temperature for 24 h, and the membrane was naturally peeled off with deionized water to obtain a polymer coated cationic membrane.
[0029] (3) Construction of polymer coated membrane electrodialysis system: The polymer coated membrane electrodialysis system includes an anode receiving chamber, a feed chamber, a cathode receiving chamber and a cathode electrode chamber connected in sequence. A polymer coated membrane anion membrane is arranged between the anode receiving chamber and the feed chamber, a polymer coated membrane cation membrane is arranged between the feed chamber and the cathode receiving chamber, an anion exchange membrane is arranged between the cathode receiving chamber and the cathode electrode chamber, and electrode plates are arranged outside the cathode electrode chamber and the anode receiving chamber, which are connected to the negative electrode and the positive electrode of the power supply respectively. + Transport to cathode, GaCl4 - 、FeCl4 - Transport to the anode. The chamber volume is 25mL and the effective membrane area is 25cm 2 .
[0030] (4) The feed liquid, receiving liquid, and electrode liquid are pumped into the corresponding chambers for circulation; the feed liquid is pumped into the feed chamber, the anode receiving liquid is pumped into the anode receiving chamber, the cathode receiving liquid is pumped into the cathode receiving chamber, and the cathode electrode liquid is pumped into the cathode electrode chamber; a DC voltage is applied on both sides of the polymer coated membrane electrodialysis system, and under the action of electric drive and the selective permeation of the polymer coated membrane, the directional migration and separation and enrichment of multiple ions are achieved. Specifically, a 5V voltage is used for an 8h transmission experiment, and the feed liquid is Fe 3+ Concentration 4.8g / L, Al 3+ Concentration 20g / L, Ga 3+ Concentration 100mg / L, Li + A mixed solution with a concentration of 1g / L and a pH of 0.4; the anode receiving solution is a 0.1mol / L H2SO4 solution; the cathode receiving solution is a 0.1mol / L HCl solution; the cathode electrode solution is a 0.1mol / L H2SO4 solution; the feed solution is pumped into the chamber at a flow rate of 100mL / min for circulation, and 0.3mL of solution is taken from the feed chamber and the receiving chamber every 1h to analyze the ion concentration. The Fe recovery rate in the anode receiving chamber is 93.73%, and the Ga recovery rate is 81.14%; the Li concentration in the cathode receiving chamber is 494ppm, and the Li / Al ratio increases from 1:20 to 6:1.
[0031] Example 2
[0032] The difference between Example 2 and Example 1 is that: in step (4), a 3V voltage is used to carry out an 8h transmission experiment, and the feed liquid is Fe 3+ Concentration 4.8g / L, Al 3+ Concentration 20g / L, Ga 3+ Concentration 100mg / L, Li +The mixed solution had a concentration of 200 mg / L and a pH of 1, and was otherwise the same as in Example 1. The Fe recovery rate in the anode receiving compartment was 86.84%, and the Ga recovery rate was 66.31%; the Li concentration in the cathode receiving compartment was 129 ppm, and the Li / Al ratio was increased from 1:100 to 3:1.
[0033] Example 3
[0034] The difference between Example 3 and Example 1 is that: in step (4), a 3V voltage is used for an 8h transmission experiment, the anode receiving solution is a 0.5mol / L H2SO4 solution; the cathode receiving solution is a 0.5mol / L HCl solution, and other than that, the same as Example 1. The Fe recovery rate in the anode receiving chamber is 96.3%, and the Ga recovery rate is 83.7%; the Li concentration in the cathode receiving chamber is 483.4ppm, and the Li / Al ratio is increased from 1:20 to 4.3:1.
[0035] Example 4
[0036] The difference between Example 4 and Example 1 is that: in step (2), when preparing the polymer coated membrane cation membrane, TBP and [HOEmim][NTf2] are mixed at a volume ratio of 1:0.5, and a LiCl solution with a lithium ion concentration of 1 g / L is added at an O / A ratio of 1:1. After stirring for 30 minutes, centrifugation is performed to obtain an organic phase (TBP-[HOEmim][NTf2]-Li) with a lithium loading concentration of 0.936 g / L as a carrier. In step (4), a 3 V voltage is used for an 8 h transmission experiment, and the feed liquid is Fe 3+ Concentration 4.8g / L, Al 3+ Concentration 20g / L, Ga 3+ Concentration 100mg / L, Li + The mixed solution had a concentration of 200 mg / L and a pH of 0, and was otherwise the same as in Example 1. The Fe recovery rate in the anode receiving compartment was 87.53%, and the Ga recovery rate was 69.32%; the Li concentration in the cathode receiving compartment was 25 ppm, and the Li / Al ratio was increased from 1:100 to 0.2:1.
[0037] Example 5
[0038] The difference between Example 5 and Example 1 is that 0.615 g PVDF and 0.485 g TBP-[HOEmim][NTf2]-Li are used in the preparation of the polymer-coated cation membrane in step (2), and other than that, the same as in Example 1. The Fe recovery rate in the obtained anode receiving chamber is 92.21%, and the Ga recovery rate is 80.33%; the Li concentration in the cathode receiving chamber is 306 ppm, and the Li / Al ratio is increased from 1:20 to 3.6:1.
[0039] Example 6
[0040] The difference between Example 6 and Example 1 is that: 0.75g PVDF, 0.20g Aliquat 336 and 0.05g 2-NPOE are used in the preparation of the polymer coated film anion membrane in step (1); 0.55g PVDF and 0.55g TBP-[HOEmim][NTf2]-Li are used in the preparation of the polymer coated film cation membrane in step (2); 3V voltage is used for 8h transmission experiment in step (4), and other than that, it is the same as Example 1. The Fe recovery rate in the obtained anode receiving chamber is 65.7%, and the Ga recovery rate is 51.3%; the Li concentration in the cathode receiving chamber is 243ppm, and the Li / Al ratio is increased from 1:20 to 4.2:1.
[0041] Example 7
[0042] The difference between Example 7 and Example 1 is that: in step (1), 0.8 g PVDF, 0.15 g Cyphos IL 101 and 0.05 g T2EHP are used in the preparation of the polymer coated membrane anion membrane; in step (2), TIBP and [HOEmim][NTf2] are mixed in a volume ratio of 1:1, and a LiCl solution with a lithium ion concentration of 6 g / L is added in an O / A ratio of 1:1. After stirring for 30 minutes, the phases are separated by centrifugation to obtain an organic phase (TIBP-[HOEmim][NTf2]-Li) with a lithium loading concentration of 0.733 g / L as a carrier; 0.5 g PVDF and 0.6 g TIBP-[HOEmim][NTf2]-Li are mixed and dissolved in 10 mL DMF, and magnetic stirring is performed for 12 hours to obtain a casting solution; in step (4), the anode receiving solution is 0.3 mol / L H2SO4 solution; the cathode receiving solution was 0.3 mol / L HCl solution, except for the above, the same as in Example 1. The Fe recovery rate in the anode receiving chamber was 56.2%, and the Ga recovery rate was 48.7%; the Li concentration in the cathode receiving chamber was 194 ppm, and the Li / Al ratio was increased from 1:20 to 0.2:1.
[0043] Example 8
[0044] The difference between Example 8 and Example 1 is that: in step (1), 0.7 g PVDF, 0.25 g Aliquat 336 and 0.05 g 2-NPPE are used in the preparation of the polymer coated membrane anion membrane; in step (2), N503 and [HOEmim][NTf2] are mixed in a volume ratio of 1:0.2, and a LiCl solution with a lithium ion concentration of 3 g / L is added at an O / A ratio of 1:1. After stirring for 30 minutes, centrifugal separation is performed to obtain an organic phase (N503-[HOEmim][NTf2]-Li) with a lithium loading concentration of 1.51 g / L as a carrier; 0.5 g PVDF and 0.6 g N503-[HOEmim][NTf2]-Li are mixed and dissolved in 10 mL DMF, and magnetic stirring is performed for 12 hours to obtain a casting solution; in step (4), the voltage is set to 4 V, and the feed solution is Fe 3+ Concentration 4.8g / L, Al 3+ Concentration 20g / L, Ga 3 + Concentration 100mg / L, Li + The mixed solution had a concentration of 100 mg / L and a pH of 0.4, and was otherwise the same as in Example 1. The Fe recovery rate in the anode receiving compartment was 89.11%, and the Ga recovery rate was 83.48%; the Li concentration in the cathode receiving compartment was 26 ppm, and the Li / Al ratio increased from 1:200 to 0.07:1.
[0045] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
Claims
1. A method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step, characterized in that: The following steps are involved: Step 1: Prepare a polymer-coated anion membrane that selectively transmits iron and gallium; Step 2: preparing a polymer-coated cation membrane for selective lithium transport; Step 3: Establishing a polymer-coated membrane electrodialysis system; Step 4: Use a polymer-coated membrane electrodialysis system to treat the hydrochloric acid leaching solution of industrial solid waste containing aluminum, iron, lithium and gallium.
2. The method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step according to claim 1, characterized in that: The step 1 specifically includes: mixing and dissolving a base polymer, a carrier, and a plasticizer in an organic solvent to obtain a casting solution; coating the casting solution on a glass plate, and taking it out after the solvent evaporates to obtain a polymer coated film anion membrane; wherein the base polymer is one or more of polyvinyl chloride, polyvinylidene fluoride, polyvinylidene fluoride-co-hexafluoropropylene, the carrier is one or more of methyl trioctyl ammonium chloride and trihexyl (tetradecyl) chlorophosphine, the plasticizer is one or more of 2-nitrophenyl octyl ether, trioctyl phosphate, and 2-nitrophenyl pentyl ether, and the mass percentages of the base polymer, the carrier, and the plasticizer in the polymer coated film anion membrane are 70% to 80%, 15% to 25%, and 0 to 5%, respectively.
3. The method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step according to claim 1, characterized in that: The step 2 specifically includes: mixing a base polymer and a carrier and dissolving them in an organic solvent to obtain a casting solution; coating the casting solution on a glass plate, and taking it out after the solvent evaporates to obtain a polymer-coated cation film; wherein the base polymer is one or more of polyvinyl chloride, polyvinylidene fluoride, polyvinylidene fluoride-co-hexafluoropropylene, and the carrier is an organic phase loaded with lithium ions, and the mass percentages of the base polymer and the carrier in the polymer-coated cation film are 45% to 65% and 35% to 55%, respectively.
4. The method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step according to claim 3, characterized in that: The preparation method of the organic phase loaded with lithium ions is as follows: one or more of tributyl phosphate, triisobutyl phosphate, N,N-bis(1-methylheptyl)acetamide and 1-hydroxyethyl-3-methylimidazole bis(trifluoromethanesulfonyl)imide salt are mixed at a volume ratio of 1:0.2 to 1:5, and then mixed with a LiCl solution with a lithium ion concentration of 1 g / L to 6 g / L at a volume ratio of 1:1, stirred, and centrifuged to separate phases to obtain the organic phase.
5. A method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step according to claim 2 or 3, characterized in that: The organic solvent is one or more of tetrahydrofuran, N,N-dimethylformamide and dichloromethane.
6. A method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step according to claim 2 or 3, characterized in that: The solvent evaporation conditions are: evaporation at 22±3°C for 12 to 24 hours.
7. The method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step according to claim 1, characterized in that: The polymer coated membrane electrodialysis system in step 3 comprises an anode receiving chamber, a feed chamber, a cathode receiving chamber and a cathode electrode chamber which are connected in sequence, a polymer coated membrane anion membrane is arranged between the anode receiving chamber and the feed chamber, a polymer coated membrane cation membrane is arranged between the feed chamber and the cathode receiving chamber, an anion exchange membrane is arranged between the cathode receiving chamber and the cathode electrode chamber, and electrode plates are arranged outside the cathode electrode chamber and the anode receiving chamber, which are respectively connected to the negative electrode and the positive electrode of the power supply.
8. The method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step according to claim 1, characterized in that: The specific process of step 4 is: pumping the feed liquid, receiving liquid and electrode liquid into the corresponding chambers for circulation; wherein the feed liquid is pumped into the feed chamber, the anode receiving liquid is pumped into the anode receiving chamber, the cathode receiving liquid is pumped into the cathode receiving chamber, and the cathode electrode liquid is pumped into the cathode electrode chamber; applying a DC voltage on both sides of the polymer coated membrane electrodialysis system, and under the action of electric drive and the selective permeation of the polymer coated membrane, the directional migration and separation and enrichment of multiple ions are achieved.
9. The method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step according to claim 1, characterized in that: The feed liquid is a hydrochloric acid leaching solution of industrial solid waste containing Al, Fe, Li and Ga, with a pH value of 0-1, a cathode receiving liquid is a 0.1-0.5 mol / L HCl solution, an anode receiving liquid is a 0.1-0.5 mol / L H2SO4 solution, and a cathode electrode liquid is a 0.1 mol / L H2SO4 solution; each feed liquid is pumped into the chamber at a flow rate of 100 mL / min to circulate in each chamber; the current density of the electrodialysis process is controlled to be 7-20 mA / cm 2 .
10. The method for separating aluminum iron lithium gallium from industrial solid waste hydrochloric acid leachate in one step according to claim 1, characterized in that: The industrial solid waste is one or more of coal gangue, fly ash and red mud.
Citation Information
Patent Citations
Methods for extracting lithium from fly ash
CN108265176B
A method for the co-extraction of aluminum-iron-lithium-gallium from an acidic system of high-alumina solid waste
CN115418478B
Method for separating multiple valuable metals in secondary resource leachate in one step
CN115418676A